EFEKTIFITAS PENGGUNAAN HANDPHONE DALAM MENINGKATKAN MINAT BERKONSULTASI SISWA SMP (STUDI KASUS DI SMP NEGERI 2 BELO) - khairunnisa khairunnisa (Guiding World : Jurnal Bimbingan dan Konseling, 2019)
The implementation of guidance and counseling services should take place in comfortable and conducive conditions. Guidance and counseling is expected to develop one's potential and competence in the community to be able to fulfill their duties optimally. In addition, in helping individuals overcome various problems that can interfere with its development[1]. This research is motivated by many students who feel afraid when called by counseling and guididance teachers, let alone have to come to the counseling room to consult or sharing probem. The lack of interest in consulting students was allegedly due to various factors. One of them is due to the lack of socialization conducted by counseling and guidance teachers in introducing what and how counseling and guidance is. If this socialization can be carried out well, it will at least give a clear picture to students that the counseling and guidance is present as a forum and student's friend while studying. Efforts that can be done include: Able to familiarize yourself with students and be able to position yourself as friends, and improve counseling skills so as to improve verbal and non verbal communication skills, express problems, understand problems and accept students. So that these efforts are maximized, the counseling and guidance teacher can use the media as a tool, one of which can be through the help of media, namely mobile phones. To get rid of these feelings, the BK teacher uses mobile media as a communication tool to consult with students. This study aims to determine whether the use of mobile phones is effective in increasing the interest in consulting students of STATE 2ND JUNIOR HIGH SCHOOL. The approach used in this study is qualitative research that is shown to describe and describe existing phenomena that are scientific[2]. While the type of research used is descriptive research. This research was conducted in SMP NEGERI 2 BELO, the research subjects were 2 counseling and guidance teachers and 5 students who had used mobile phones in consulting services. The method of data collection is done by observation, interviews, and documentation. Analysis of data using qualitative descriptive by interpreting the data obtained. The research shows that the process of using mobile phones in increasing the interest in consulting students of SMP NEGERI 2 BELO is carried out in stages, starting from the preparation stage consisting of media and socialization selection, then the implementation stage consists of identification, giving outreach and evaluating both the process and the results. Based on the results of the study, the researchers can conclude that the use of mobile phones is effective in increasing the interest in consulting students of SMP Negeri 2 BELO